Sustainable economic development and the influence of information technologies : dynamics of knowledge society transformation - Karatas, Muhammed, 1972-; Tunca, Mustafa Zihni, 1972- (Hershey, PA : Information Science Reference, 2010)
'This book provides relevant theoretical frameworks and the latest empirical research findings in the area of information technology as it relates to sustainable economic development and the development of knowledge societies'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Sustainable development -- Developing countries; Information technology -- Developing countries